Modeling of extrusion-based additive manufacturing for pelletized thermoplastics: Analytical relationships between process parameters and extrusion outcomes. (April 2023) - Pricci, Alessio; de Tullio, Marco D.; Percoco, Gianluca
Abstract: Recent developments in additive manufacturing are moving toward a new trend in material extrusion (ISO/ASTM 52910:2018), namely, the possibility of printing thermoplastic strands directly from pellets. Pellet additive manufacturing (PAM) is a relatively new manufacturing process that realizes the aforementioned goal. Consequently, the development of models describing the behavior of the entire process remains a matter of research. The present study aims to propose a systematic and parametric analysis based on an analytical model that describes the entire process, from solid pellet conveying to the deposition of molten strands. First, a mathematical model that analytically describes the behavior of a system consisting of a single-screw extruder, a coupling element, and an extrusion nozzle is presented, without considering the effect of the printed strand. The proposed approach allows the calculation of important process variables, such as the mass flow rate, melting profile, and pressure profile for a given screw speed. An experimental setup aimed at predicting the mass flow rate of a real single-screw extruder and computational fluid dynamics simulations were used to validate the theory presented. The model was then extended to the PAM process, where an additional counterpressure exists because of the strand being deposited on the build plate. The goal is to predict the screw-speed which allows to extrude a prescribed mass flow rate. Subsequently, the effects of the printing nozzle speed and layer height on the process outcomes were investigated. A good agreement with similar trends already predicted in modeling the counterpressure in fused filament fabrication was found.